The effects of a fat loss supplement on resting metabolic rate and hemodynamic variables in resistance trained males: a randomized, double-blind, placebo-controlled, cross-over trial - Campbell, B.; Colquhoun, R.; Zito, G.; Martinez, N.; Kendall, K.; Buchanan, L.; Lehn, M.; Johnson, M.; St. Louis, C.; Smith, Y.; Cloer, B. (Journal of the International Society of Sports Nutrition, 2016)
Background: While it is known that dietary supplements containing a combination of thermogenic ingredients can increase resting metabolic rate (RMR), the magnitude can vary based on the active ingredient and/or combination of active ingredients. The purpose of this study was to examine the effects of a commercially available thermogenic fat loss supplement on RMR and hemodynamic variables in healthy, resistance trained males.